Tìm x biêt:
(x-5)4=(x-5)6
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a\times5:6=25\)
\(a\times5=25\times6\)
\(a\times5=150\)
\(a=150:5\)
\(a=30\)
\(a\times5:6=25\\ a\times\dfrac{5}{6}=25\\ a=25:\dfrac{5}{6}\\ a=25\times\dfrac{6}{5}\\ a=30\)
x/5 + x2 + x/5:1/2=13
x/5 + x.2 + x/5 x 2 = 13
x/5.(1 + 2 ) + 2x = 13
x/5 .3 +2x = 13
3x/5 + 2x = 13
3x + 10x = 65
13x = 65
x = 65 : 13
x = 5
1,-12 + x = 5x - 20
-12 + 20 = 5x - x
8 = 4x
x = 2
2, 7x - 4 = 20 + 3x
7x - 3x = 20 + 4
4x = 24
x = 6
3 , 5x - 7 = -21 - 2x
5x + 2x = -21 + 7
7x = -14
x = -14 : 7 = -2
4 , x + 15 = 20 - 4x
x + 4x = 20 - 15
5x = 5
x = 5 : 5 = 1
5, 17 - x = 7 - 6x
-x + 6x = 7 - 17
5x = -10
x = -10 : 5 = -2
Số số hạng là :
\(\left(x-2\right):2+1=x:2-1+1=x:2\) (số hạng)
Tổng trên là :
\(\left(x+2\right).x:2:2=42\)
\(\left(x+2\right).x=42.2.2\)
\(\left(x+2\right).x=168\)
\(\left(x+2\right).x=14.12\)
Vậy x = 14
a) \(\frac{1}{2}+\frac{2}{3}x=\frac{4}{5}\)
\(x=\frac{\left(\frac{4}{5}-\frac{1}{2}\right)}{\frac{2}{3}}\)
\(x=\frac{9}{20}\)
b) \(\left|x+\frac{3}{4}\right|-\frac{1}{2}=0\)
\(\left|x+\frac{3}{4}\right|=0+\frac{1}{2}\)
\(\left|x+\frac{3}{4}\right|=\frac{1}{2}\)
\(\Rightarrow\hept{\begin{cases}x+\frac{3}{4}=\frac{1}{2}\\x+\frac{3}{4}=-\frac{1}{2}\end{cases}\Rightarrow\hept{\begin{cases}x=\frac{-1}{4}\\x=\frac{-5}{4}\end{cases}}}\)
Vậy x=-1/4 hoặc x=-5/4
c) \(\left(x+\frac{1}{3}\right)^3=\frac{-1}{8}\)
\(\Leftrightarrow x+\frac{1}{3}=\frac{-1}{8}=\frac{\left(-1\right)^3}{2^3}=\frac{-1}{2}\)
\(x=\frac{-1}{2}-\frac{1}{3}\)
\(x=\frac{-5}{6}\)
\(\frac{1}{2}+\frac{2}{3}x=\frac{4}{5}\)
\(\frac{2}{3}x=\frac{4}{5}-\frac{1}{2}\)
\(\frac{2}{3}x=\frac{3}{10}\)
\(x=\frac{3}{10}:\frac{2}{3}\)
\(x=\frac{9}{20}\)
b) l x + 3/4 l - 1/2 = 0
l x + 3/4 l = 1/2
TH1 : \(x+\frac{3}{4}\le0\) TH2: \(x+\frac{3}{4}\ge0\)
=> \(x+\frac{3}{4}=-\frac{1}{2}\) => \(x+\frac{3}{4}=\frac{1}{2}\)
\(x=-\frac{1}{2}-\frac{3}{4}\) \(x=\frac{1}{2}-\frac{3}{4}\)
\(x=-\frac{5}{4}\) \(x=-\frac{1}{4}\)
c) ( x + 1/3 )3 = ( -1/8 )
( x + 1/3 ) 3 = ( -1/3 )3
=> x + 1/3 = -1/3
x = -1/3 - 1/3
x = -2/3